Stock Return: Debt to Equity Ratio (DER) and Return on Equity (ROE) in Real Estate and Property Industrial Companies - Malahayati, Rina; Tahir, Muhammad; Hasan, Muridha (Budapest International Research and Critics University, 2022)
This study aims to determine the effect of Debt to Equity Ratio (DER) and Return on Equity Ratio (ROE) on stock returns. This research includes associative research. The population of this study are real estate and property industry companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2018 period. Determination of the sample using purposive sampling method and there are 26 companies that meet the criteria as research samples. The results showed that the Debt to Equity Ratio (DER) had a negative but not significant effect on stock returns and Return on Equity (ROE) had a positive effect on stock returns.